Heart Failure in Congenital Heart Disease: From Fetus to Adult - Shaddy, Robert. E.; SpringerLink (Online service) (London : Springer London, 2011)
Survival outcomes for patients with congenital heart disease have greatly improved over the last two decades. Because of better and longer survival in these patients who often have abnormal ventricular morphology, the incidence of heart failure in this patient population has also increased. Although there is a significant evidence base for the treatment of heart failure in adults, the evidence base for treating children and adults with congenital heart disease is significantly less. Heart Failure in Congenital Heart Disease: From Fetus to Adult describes the current state-of-the-art and in-depth analysis of the topic of heart failure in patients with congenital heart disease. In this rapidly growing population, this book provides both evidence-based and practical recommendations for the management of heart failure signs and symptoms. Each aspect of heart failure in the patient with congenital heart disease has been presented, making this the ideal reference for all cardiologists and pediatric cardiologists who are required to manage these patients.
Keywords: Medicine; Internal medicine; Cardiology; Pediatrics; Heart -- Surgery; Medicine & Public Health; Cardiology; Pediatrics; Internal Medicine; Cardiac Surgery